Assessing mercury and lead pollution in the Ankobra estuary due to artisanal mining activities: Implications for water quality and aquatic life - Mary Opeyemi Adebote; Joseph Aggrey-Fynn; Paul Kojo Mensah (PLoS ONE, 2025)
Artisanal and small-scale gold mining, “Galamsey” as it is called in Ghana, within the Ankobra estuary has impacted the water quality, fish health and other aquatic organisms. This paper presents a study investigating the concentrations of mercury and lead in water, sediments, gills and liver of Chrysichthys nigrodigitatus of the Ankobra estuary. Bimonthly sampling between December 2020 and June 2021 was conducted at nine locations along the estuary. Physicochemical parameters such as temperature, dissolved oxygen, pH and turbidity were determined in situ using the EUTECH Multi-Parameter probe. A total of 36 water samples, 36 sediment samples and 120 fish samples were collected. Mercury (Hg) and lead (Pb) concentrations in the samples were measured using Atomic Absorption Spectrophotometry (AAS), employing appropriate techniques for each metal. Results showed that the physicochemical parameters of water, except for turbidity, were within the acceptable limits for aquatic life, based on the United States Environmental Protection Agency water quality criteria. Mercury and lead concentrations in water and fish samples exceeded United States Environmental Protection Agency guideline thresholds. In sediments, mercury levels surpassed both average shale values and ecological risk thresholds (ERM = 0.71 mg/kg), indicating high ecological risk, while lead remained below the ERL (46.7 mg/kg), suggesting low risk. Mercury and lead concentration in fish, water and sediments differ significantly (P < 0.05) across locations and between matrices (water, sediment, and fish organs). High bioaccumulation factors (BAFs) were recorded for both metals in fish. The BAF of mercury in fish-to-water samples was greater than in fish-to-sediment samples. In contrast, the bioaccumulation factor of lead was greater than in sediments compared to water. The study revealed that Ankobra estuary is polluted with mercury and lead and all necessary regulations should be enforced on the activities of artisanal miners to curb this menace.